SCIENTIFIC AND THEORETICAL FOUNDATIONS FOR THE DEVELOPMENT OF MASS SPORTS AMONG UNIVERSITY STUDENTS - Utashev Khasan Nematullaevich (Sciental Journals Publishing, 2025)
This article analyzes the scientific and theoretical foundations for the development of mass sports among university students. The study examines the social significance of mass sports, students’ physical activity, motivation, and the state of sports infrastructure. It also proposes solutions to existing problems and recommendations for their implementation. The article highlights the role and importance of mass sports in forming a healthy lifestyle among students and suggests scientifically grounded approaches to enhance the sports culture in higher education institutions.
Keywords: Higher education institutions, students, mass sports, physical activity, sports infrastructure, motivation, healthy lifestyle, sports culture, scientific-theoretical foundations